PENGARUH HARGA, KUALITAS PRODUK DAN CITRA MEREK TOKO SEMBAKO MENTARI DI JAKARTA SELATAN TERHADAP KEPUTUSAN PEMBELIAN - Ella Ratna Lesatri; Alaidin Rapani; Kadek Ayu Susiani Dewi (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2022)
The purpose of this study was to determine the effect of price, product quality and brand image of Mentari Grocery Stores in South Jakarta on purchasing decisions. Forms of data collection with questionnaires and libraries. The questionnaire is a list of statements that include all statements and questions that will be used to obtain data. Literature studies are carried out by searching and examining existing data and literature or theories. The results showed that the questionnaire was distributed to 80 respondents to find out whether there is an effect of price, product quality and brand image of Mentari Grocery Stores in South Jakarta on purchasing decisions. This data analysis technique uses SPSS 25 which shows that the price variable (X1) partially has a significant positive effect on purchasing decisions (Y). Product quality variable (X2) partially has a significant positive effect on purchasing decisions (Y). Brand image variable (X3) partially has a significant positive effect on purchasing decisions (Y). Price variable (X1), product quality (X2) and brand image variable (X3) have a significant positive effect on the purchase decision variable (Y). Judging from the value of the correlation coefficient (R) of 0.820, which means that there is a strong correlation or relationship between price, product quality and the brand image of Mentari Grocery Stores in South Jakarta on purchasing decisions. Adjusted R2 value is 0.659 or equal to 65.9%, this shows that the percentage influence of price, product quality and brand image of Mentari Grocery Stores in South Jakarta combined has a simultaneous effect on purchasing decisions of 65.9% while the remaining 34.1 % (from 100% - 65.9%) is influenced by other variables not included in this research model